The Effect of Warm Mixture Asphalt for AsphaltConcrete (ACWC) with the added of Asbuton on Asphalt Quality - Sartika Nisumanti; Febryandi Febryandi; Syntia Dwi (International Conference on Multidisciplinary Research, 2021)
This study aims to analyse a warm mix of asphalt with the addition of asbuton to measure theoptimum grain content of asbuton. The research was conducted with 3% asbuton content, variationsin asphalt content of 5%,5.5%,6%, 6.5%,7%. AC-WC mix type uses 60/70 penetration using theMarshall method. The results showed that 5% asphalt content showed a lower level of stability1307.84 kg and a higher level of stability 1649.76 kg with an asphalt content of 6.5%. Correction rateof stability ≥800 kg. While the variation of AC-WC warm asphalt mixture with the addition of butonhas an effect on the VIM value in the mixture. Parameters that do not meet the requirements of theVIM value are asphalt mixture content of 5% as much as 6.03% and 5.5% of 5.89% with a standardrange of asphalt content of 3.5-5.5%. The effect of warm asphalt mixture for AC-WC with theaddition of buton has a VMA value that meets the standard VMA value ≥15. This shows that thehigher the asphalt content, the higher the cavity in the asphalt mixture aggregate. The lowest flowvalue was at 7% asphalt content of 4.74 mm, while the lowest flow rate of 5% asphalt content was3.33 mm. The warm asphalt mixture for AC-WC with asbuton added material has an optimum asphaltcontent of 6.5%. Keywords: Asbuton, Asphalt Penetration 60/70,Marshall Test